Kasata klasztoru Cystersów i pierwsze lata duszpasterstwa diecezjalnego w Obrze (1835-1840) - Zając, Paweł (Ecclesia. Studia z Dziejów Wielkopolski, 2011)
The Cistercian monastery in Obra was suppressed by the Prussian government in 1835-1836, forty years after the last partition of Poland. This meant the end of the presence of the Cistercian religious order in Obra after six centuries of tradition which to a great extent shaped the village and surrounding areas. The pastoral work in Obra needed to be reorganized and the diocesan clergy took over the former Cistercian responsibilities. Diocesan priests became pastors of the parish for nearly 100 years, until 1926-1927, when another religious congregation – Oblates of Mary Immaculate – established themselves in the monastery and the parish. The article describes in detail the events related to the suppression of the Cistercian monastery and its consequences – both material and personal – for the parish. It was to be an introduction to an extended period of 90 years of diocesan pastoral ministry in Obra.